2013
DOI: 10.2135/cropsci2013.01.0041
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Dynamics of Maize Nitrogen Uptake and Partitioning in Response to Plant Density and Nitrogen Stress Factors: II. Reproductive Phase

Abstract: Improved plant N utilization and partitioning is critical for future improvements in maize (Zea mays L.) grain yield (GY). The overall research objective was to gain understanding of the physiological mechanisms underpinning biomass (BM), N uptake partitioning, and GY processes during the reproductive period for two maize hybrids grown at varying plant density (PD) (low is 54,000 plant ha−1, medium is 79,000 plants ha−1, and high is 104,000 plants ha−1) and N inputs (low is 0 kg N ha−1, medium is 112 kg N ha−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
50
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 66 publications
7
50
1
Order By: Relevance
“…Despite high grain yield, N uptake levels at silking and post-silking in our study were less than the levels reported in previous studies Liu et al, 2014b;Mu et al, 2015;Zheng et al, 2016;Cao et al, 2017;Zhou et al, 2017). Improved plant N utilization and partitioning is critical for improvements in maize grain yield (Ciampitti et al, 2013b). Previous studies also showed that N demand post-silking increases significantly when the grain yield exceeded 15 Mg ha −1 (Ding et al, 2005;Huang et al, 2007;Ciampitti and Vyn, 2013a), which was in accordance with our observation.…”
Section: Discussion Nitrogen Uptake and Grain Yieldsupporting
confidence: 83%
See 1 more Smart Citation
“…Despite high grain yield, N uptake levels at silking and post-silking in our study were less than the levels reported in previous studies Liu et al, 2014b;Mu et al, 2015;Zheng et al, 2016;Cao et al, 2017;Zhou et al, 2017). Improved plant N utilization and partitioning is critical for improvements in maize grain yield (Ciampitti et al, 2013b). Previous studies also showed that N demand post-silking increases significantly when the grain yield exceeded 15 Mg ha −1 (Ding et al, 2005;Huang et al, 2007;Ciampitti and Vyn, 2013a), which was in accordance with our observation.…”
Section: Discussion Nitrogen Uptake and Grain Yieldsupporting
confidence: 83%
“…Therefore, adequate N supplementation and uptake by plants during grain filling in this study may have been a primary factor contributing to the highest yield occurring with high plant density, which is in accordance with our hypothesis. Improved plant N utilization and partitioning is critical for improvements in maize grain yield (Ciampitti et al, 2013b). In the present study, N req , to some extent, reflected NUE.…”
Section: Discussion Nitrogen Uptake and Grain Yieldmentioning
confidence: 52%
“…In addition to the genetic improvements in NUE, tolerance to increased plant density is one of the most valuable agronomic advances since the development of the maize hybrid (Duvick, 1977). Maize yield increases across different N fertilizer and plant density conditions were associated with greater N uptake and greater ear sink strength (kernel weight and number) during reproductive development (Ciampitti et al, 2013). The kernel weight component has been found to be more related to the yield increases than to kernel number, and was associated with a longer grain‐filling period, improved biomass remobilization during reproductive development, enhanced stress tolerance to N loss, and higher plant densities (Chen et al, 2016).…”
mentioning
confidence: 99%
“…More integrated‐approaches (at plant‐ and community‐scales) based on physiological‐driven changes beyond plant density stress tolerance alone (e.g., modifications in plant processes such as nutrient partitioning, kernel establishment, ear size, number of ears per plant, among others) should be pursued. Formation of kernels row per ear starts early during the vegetative period (V5 stage) with final ear size and potential kernel number defined around mid‐to‐late vegetative (V12 stage); unbalanced nutrient uptake early during maize growing season can affect plant nutrient concentration, biomass, and produce early abortion of the potential number of kernels (Ciampitti et al, 2013b). Nitrogen can affect ear size and the final number of kernels.…”
Section: Resultsmentioning
confidence: 99%
“…Although potential kernel number (before flowering) was slightly reduced by N stress, post‐flowering abortion with low N reduced the final kernel number much more (Ciampitti et al, 2013b). The effects of N, P, and K nutrients on biomass, yield, and final nutrient partitioning was also recently investigated by Ciampitti et al (2013a, 2013b); these studies documented a proportionality for P and K responses to biomass and N partitioning (vegetative to reproductive organs) patterns from early flowering stage until maturity. Yield improvement based on optimizing plant nutrient balance ratios should be focused on understanding complex and physiological plant growth and nutrient uptake pathways.…”
Section: Resultsmentioning
confidence: 99%